How do you solve by substitution #x-y+-15# and #x+y=-5#?

Answer 1
Assuming the first component should have (#=-#) instead of (#+-#)
[1]#color(white)("XXXX")##x-y = -15# [2]#color(white)("XXXX")##x+y=-5#
Rearranging the terms of [1] [3]#color(white)("XXXX")##x= y-15#
Substituting #(y-15)# for #x# into [2] [4]#color(white)("XXXX")##(y-15) + y = -5# [5]#color(white)("XXXX")##y=5#
Substituting #5# for #y# back in [1] [6]#color(white)("XXXX")##x - 5 = -15# [7]#color(white)("XXXX")##x = -10#
Solution: #(x,y) = (-10,5)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the system of equations by substitution:

  1. Solve one of the equations for one variable in terms of the other variable.
  2. Substitute this expression into the other equation.
  3. Solve the resulting equation for the remaining variable.
  4. Once you have found the value of one variable, substitute it back into one of the original equations to find the value of the other variable.

Given the equations x - y = -15 and x + y = -5:

  1. From the second equation, solve for x: x = -5 - y.

  2. Substitute this expression for x into the first equation: -5 - y - y = -15.

  3. Simplify and solve for y: -5 - 2y = -15. -2y = -15 + 5. -2y = -10. y = -10 / -2. y = 5.

  4. Now that we have found the value of y, substitute it back into one of the original equations to find x. Using the second equation: x + 5 = -5. x = -5 - 5. x = -10.

So, the solution to the system of equations is x = -10 and y = 5.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To solve the system of equations (x - y = -15) and (x + y = -5) by substitution, we can isolate one of the variables in one equation and substitute it into the other equation.

First, isolate (x) in the second equation: [x + y = -5] [x = -5 - y]

Now substitute (x = -5 - y) into the first equation: [-5 - y - y = -15] [-5 - 2y = -15]

Add 5 to both sides: [-2y = -10]

Divide both sides by -2: [y = 5]

Now substitute (y = 5) into (x = -5 - y): [x = -5 - 5] [x = -10]

So, the solution to the system of equations is (x = -10) and (y = 5).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7